Family Policy in Austria in Comparison: How to Reach Sustainability? - Gudrun Biffl (Austrian Institute of Economic Research (WIFO), 2008)
Family policy is getting increasing public policy attention in the EU as a result of population ageing and the challenge of the sustainability of economic growth. It is being recognised that a sustainable rise in the fertility rate is needed in order to put a break on population ageing. Immigration can postpone but not stem the tide of ageing. In consequence, research into the reasons for the decline in the fertility rate and the role of public policy in promoting fertility gain momentum. There is growing evidence that social and economic policies do have an important role to play in raising fertility. Properly devised, they allow a better balance of market and family work and raise the propensity to invest in higher education and training, thereby furthering the sustainability of economic growth and wellbeing of the society.
Keywords: 330; sustainable family policy; fertility; labour force participation; work-life balance; Familienpolitik; Nachhaltigkeit; Fertilität; Erwerbstätigkeit; Familie-Beruf; Österreich